Meeting the Third World challenge - MacBean, Alasdair I.; Balasubramanyam, V. N.; Trade Policy Research Centre (London : Macmillan Press for the Trade Policy Research Centre, 1976)
This book examine some of the effect of these various crises on the third world
Includes bibliographical references and index.
oo 22/01/2019
Loans
Keywords: International economic relations; Developing countries